Role of Technology in Driving Financial Inclusion in Indian Banking Sector - Bhat, Vidya; K.T., Dr. Srinivas (International Journal of Scientific Research and Management (IJSRM), 2022)
Digitalization is a new buzz world today. Over the past few years, India has been witnessing an extraordinary level of digitization and digital disruption, which has completely transformed the way in which public services are delivered. Technology has become a prominent theme which is driving inclusion across the financial services, education and healthcare ecosystem for all the citizens of India. As a result of the powerful JAM trinity of Jan Dhan Bank Accounts, the biometric Aadhar Card and hundreds of millions of mobile phones, financial inclusion has become a reality for the citizens of India. This has been speeding up by the Unified Payments Interface (UPI) which has witnessed incredible adoption. UPI recorded over 22.33 billion transactions worth over ₹ 41.03 trillion at the end of FY 2020-21. The platform approach taken by the government in conceptualizing UPI has resulted in supreme payments products being developed on top of it, as a result of which payments can be made with the click of a mobile phone not just at retail outlets but also peer to peer, completely redefining the way in which money is transferred between individuals. Before UPI, the banking system is severely depending on different card system, the Real Time Gross Settlement (RTGS) system and transactions through National Electronic Funds Transfer (NEFT) system to have the inclusive financial growth. The present research article discusses about the technology revolution in different payment infrastructure, tools and techniques adopted by the Indian banking sector and recognised the challenges faced by Indian banking system to have a digital financial inclusion in the country.